A pilot randomized controlled trial on the utility of gastric conditioning in the prevention of esophagogastric anastomotic leak after Ivor Lewis esophagectomy. The APIL_2013 Trial. (October 2022) - Mils, Kristel; Miró, Mònica; Farran, Leandre; Videla, Sebastian; Alba, Esther; Estremiana, Fernando; Bettonica, Carla; Aranda, Humberto
Abstract: Background: Anastomotic leakage (AL) after Ivor Lewis esophagectomy is associated with high morbidity and mortality. Preoperative gastric conditioning (GC) improves blood perfusion of the gastroplasty, one of the most important factors for anastomotic viability. This pilot randomized controlled trial aimed to evaluate the feasibility of GC before oesophageal surgery in patients with oesophageal cancer or Siewert I-II esophagogastric junction cancer, who required an Ivor Lewis esophagectomy. Materials and methods: This was a randomized (1:1), open-label, single-centre, controlled, parallel-group, pilot clinical trial. Two study groups: 1) GC-group: patients who underwent an Ivor Lewis esophagectomy and GC before surgery; 2) Surgery alone (SA)-group: patients who underwent only Ivor Lewis esophagectomy. Feasibility was assessed by means of the number of patients in whom a GC was performed, and the cumulative incidence of postoperative AL. Secondary endpoints were conduit necrosis (CN), hospital stay, morbidity, mortality, and anastomotic stricture. Results: Between 2015 and 2018, 38 patients were randomized and analysed: 20 to GC-group and 18 to SA-group. 17 GCs (85%) were successfully performed, right gastric artery occlusion failed in three patients. Morbidity after GC occurred in 5/22 patients (all Clavien-Dindo ≤ IIIa). The cumulative incidence of AL was 15.0% (3/20, 95%CI: 5.2–36.0%) in GC-group and 33.3% (6/18, 95%CI: 16.3–56.3%) in SA-group, p-value : 0.184. CN: 0/20 vs. 1/18 ( p-value: 0.474 ); surgical morbidity (Clavien-Dindo III-V): 7/20 vs. 12/18 ( p-value: 0.070 ); hospital stay (median [range] days): 12 [9–45] vs. 27.5 [10–166] ( p-value: 0.067 ). When only successful GCs (three arteries) were included for analysis, ischemia-related gastric conduit failure (AL and CN) was lower in the GC group ( p-value: 0.041 ). Conclusions: Preoperative arteriographic GC before Ivor Lewis esophagectomy is a feasible and safe procedure and seems it may reduce AL in patients with oesophageal cancer or Siewert I-II esophagogastric junction cancer. Highlights: Arteriographic gastric conditioning before oesophageal surgery may reduce anastomotic leak. For gastric conditioning to have an impact on postoperative outcomes, three arteries need to be occluded. A future RCT with the right sample size needs to be conducted to confirm the working hypothesis.